Optimization of Fenton-Like Degradation Conditions of Acid Red 14 Azo Dye Under Low Frequency Ultrasonic Irradiation - Lin, Jun-Jie; Liu, Dan; Fu, Chuan; Li, Ting-Zhen (Asian Journal of Chemistry, 2012)
Response surface methodology (RSM) was applied to evaluate individual and interactive effects of the three main independent parameters (initial pH, temperature and time of ultrasound) and optimizing the operating conditions in the process of Fenton-like reaction with low frequency ultrasonic irradiation. Analysis of variance (ANOVA) showed a high coefficient of determination value (R2 = 0.9575). Effect of experimental parameters was established by the response surface and contour plots. Results showed that degradation of acid red 14 increased with increasing temperature and reaction time of ultrasound. The interactive effects were showed among three parameters (initial pH, temperature and time of ultrasound) by keeping the other constant. The optimum initial pH, temperature and time of ultrasound were found to be 6, 35 ºC and 10 min, respectively. Under the optimal value of process parameters, high removal (> 99 %) was obtained from the proposed model for acid red 14.